Legal Protection of Intellectual Property of Insolvent Debtors in Bankruptcy Perspective - Rasji Rasji; Jeane Neltje S; Aldy Wicaksono (Ridwan Institute, 2023)
Intellectual Property can be certain patents, copyright, trademarks, industrial designs, trade secrets, and other rights that are part of the origin of the intellectual property regime. These certain intellectual property rights may be the primary asset that the debtor possesses or at least something of value. In addition, the Law No. 37 of 2004 on Insolvency and the PKPU does not specify in detail whether the property of the property is property of a thing or the right of an entity, because the law only regulates the property that is excluded or the property which is not able to be paid. The curator who wants to administer and manage the property of the bankrupt does not exist like the right has always had difficulties in evaluating the property.